WAYS TO INCREASE THE COMPETENCE OF LOCAL AUTHORITIES TO ENSURE THE STABILITY OF LOCAL BUDGET REVENUES - Meyliev Obid Rakhmatullaevich (Journals Park Publishing, 2023)
The article discusses the powers of local authorities and the basis for their increase in achieving stability in local budget revenues. The possibilities of ensuring the stability of local budget revenues based on the appointment, definition and implementation of the competencies of local authorities are substantiated. Priority strategic directions have been developed for further increasing the financial independence and responsibility of local governments when applying measures to increase local budget revenues, ensure sustainable development of territories, as well as a system of factors that determine the balance of local budgets. As a result of the study, scientific and practical recommendations were given to expand the powers of local authorities.
Keywords: local budget, budget balance of local budgets, local budget revenues, local authorities, powers of local authorities, taxes, tax revenues.